Baguio: A mismanaged evolutionary narrative of the city beautiful to the city problematic. Issue 2 (3rd July 2018) - Morley, Ian
ABSTRACT: Baguio is a medium-sized city situated in the north of the Philippines. Developed as the American colonial summer capital, its centrally located roads, public spaces, and buildings are arranged in accordance with a grand plan composed in 1905 by American architect-planner, Daniel Burnham. Given this actuality the urban fabric has a disposition that contrasts from other settlements in the country: the city's configuration is anchored to a large-sized green space (Burnham Park). In recent decades Baguio's rapid urban growth has led to the manufacture of a number of worrying environmental predicaments. These include unplanned suburban districts being formed on steep hillsides, urban density in the inner quarters being increased/greenery being removed, plus traffic congestion and air pollution increasing to such a degree that the city's air quality is now amongst the worst in the Philippines. To manage this situation the city government, headed by Mayor Mauricio Domogan, has since the 2009 Burnham Park Development Master Plan repeatedly advised that Burnham Park be utilized as a site for parking substantial numbers of motor vehicles. Notwithstanding the park being protected by heritage law, the city government stating its commitment to sustainable development, and in 2017 Baguio being the first Philippine city to receive UNESCO Creative City status, it is feared that should the city council go ahead with its intention to build multi-storey car parking structures within Burnham Park not only will the space's character be irretrievably affected but the ongoing process of environmental degradation in Baguio amplified.